The influence of antigen presentation on the generation of T-helper cells with different functions. - Waldmann, H; Pope, H (1977)
Thymocytes adoptively transferred into syngeneic irradiated recipients can be primed with antigen (KLH) to generate two types of helper function termed 'specific' and 'non-specific'. Low doses of KLH given without adjuvant generate high levels of non-specific compared to 'specific' helper T cells. Large doses of KLH given in adjuvant (FCA) generate high levels of both types of helper T cell. Explantations for this observation are discussed.